2003
DOI: 10.1080/11024159850191094
|View full text |Cite
|
Sign up to set email alerts
|

The borås experience of endoscopic thoracic sympathicotomy for palmar, axillary, facial hyperhidrosis and facial blushing

Abstract: The accuracy with which pheochromocytomas and paragangliomas can be visualized questions nowadays the routine use of abdominal approach. In selected cases of sporadic unilateral chromaffin tumours, a posterior, lateral, or even laparoscopic approach should be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(33 citation statements)
references
References 0 publications
1
29
1
2
Order By: Relevance
“…Some investigators report cases of hemothorax without details! Rex et al [4] reported four cases (0.3%), Schmidt et al [46], one case (0.5%). Lin et al [47] reported on two cases (0.1%) of hemothorax, with one requiring chest tube drainage.Doolabh et al [48] reported on three patients (1.6%) who developed bleeding complications, with one patient requiring thoracoscopic re-exploration and the other patients requiring chest tube drainage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigators report cases of hemothorax without details! Rex et al [4] reported four cases (0.3%), Schmidt et al [46], one case (0.5%). Lin et al [47] reported on two cases (0.1%) of hemothorax, with one requiring chest tube drainage.Doolabh et al [48] reported on three patients (1.6%) who developed bleeding complications, with one patient requiring thoracoscopic re-exploration and the other patients requiring chest tube drainage.…”
Section: Discussionmentioning
confidence: 99%
“…Several thoracoscopic methods have since been described, with different access sites and different operative approaches (resection of the chains or simple chain division over the ribs [4] or selective sympathectomy [5]). …”
Section: Introductionmentioning
confidence: 99%
“…ETS will greatly reduce axillary sweating but the effect is clearly inferior to that on the hands despite rather extensive denervation (T2-T4 or T5). Many patients find that ETS will move the hyperhidrosis from the armpits to the trunk (CS) causing overall satisfaction to be as low as around 60 % [12,24,50]. I therefore discourage patients with isolated axillary hyperhidrosis from ETS, especially because there are other viable treatment options.…”
Section: Hyperhidrosis S Palmar Hyperhidrosismentioning
confidence: 96%
“…In long-term followup, the satisfaction rate is reduced mainly due to remaining side effects [24]. The procedure is regretted by 3.5-11 % of patients [19,37,50].…”
Section: Hyperhidrosis S Palmar Hyperhidrosismentioning
confidence: 98%
“…Habitualmente aparece con el calor o el ejercicio sobre tórax, abdomen y muslos. En general, es bien tolerada y dismi-nuye en los siguientes meses 2,18,32,40,48,49,50,51,66 .…”
Section: Hiperhidrosis Compensatoriaunclassified